A GENDER-STRATIFIED EXAMINATION OF THE INFLUENCE OF ADVERTISING ON COSMETIC PURCHASES IN MAURITIUS - Khan, Ayesha Farooq; Riaz, Usman Ahmed; Malik, Sara Naveed (International Journal of Allied Research in Economics (IJARE), 2023)
The field of advertising has a rich history dating back to ancient civilizations like the Romans and Phoenicians, where rudimentary forms of advertisement were employed to promote events and products. Modern advertising, as defined by Kotler and Armstrong (2012), represents a stark departure from these early efforts, characterized by paid, non-personal communication via various media channels. Advertising is recognized as a critical component of the promotional mix for businesses, helping them reach a wide audience and build brand identity. This paper explores the multifaceted role of advertising in influencing consumer behavior, with a particular focus on the cosmetics industry in Mauritius